2015
DOI: 10.1016/j.jneumeth.2015.01.021
|View full text |Cite
|
Sign up to set email alerts
|

The sciatic nerve injury model in pre-clinical research

Abstract: In the pre-clinical view, the study of peripheral nerve repair and regeneration still needs to be carried out in animal models due to the structural complexity of this organ which can be only partly simulated in vitro. The far most used experimental model is based on the injury of the sciatic nerve, the largest nerve trunk in mammals. In this paper, the potential application of the sciatic nerve injury model in pre-clinical research is critically reviewed. This paper is aimed at helping researchers in properly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
88
0
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 113 publications
(93 citation statements)
references
References 123 publications
1
88
0
4
Order By: Relevance
“…The explanation about the neurotrophic factors especially functions and roles of them in the nervous system has still been increasing including embryonic and postnatal development after injury. There are many studies mention main aims of neurotrophic factor researches involved in developmental roles, plasticity in the central nervous system, and mechanisms of injury and signal transduction (1)(2)(3)(4)(5)(6)(7)(8). The objective of this review is to give an overview of neurotrophic factors and emphasize importance of what we know about the functional mechanisms by which neurotrophic factors reveal their effects from an injury response window, including axonal growth and regeneration.…”
Section: Introductionmentioning
confidence: 99%
“…The explanation about the neurotrophic factors especially functions and roles of them in the nervous system has still been increasing including embryonic and postnatal development after injury. There are many studies mention main aims of neurotrophic factor researches involved in developmental roles, plasticity in the central nervous system, and mechanisms of injury and signal transduction (1)(2)(3)(4)(5)(6)(7)(8). The objective of this review is to give an overview of neurotrophic factors and emphasize importance of what we know about the functional mechanisms by which neurotrophic factors reveal their effects from an injury response window, including axonal growth and regeneration.…”
Section: Introductionmentioning
confidence: 99%
“…However, this study was the first to demonstrate that selenium has a neuroprotective effect on peripheral nerve injury in rats. In empirical studies, the models using sciatic nerve mechanical compression have been used commonly (3). In these studies, mechanical compression of the sciatic nerve has been created by different compression devices (4,(20)(21)(22).…”
Section: Discussionmentioning
confidence: 99%
“…These pathophysiological changes are associated with ischemia, which develops as a result of direct mechanical damage to the peripheral nerves, cessation of the axoplasmic flow or compression of vascular structures feeding peripheral nerves due to compression (2). Mechanical compression of the sciatic nerve has been applied in experimental studies, and after a crush injury of the sciatic nerve, they may be used to test the effectiveness of a therapeutic agent in nerve regeneration (3). The Yasargil aneurysm clip has been described as a compression device for applying crush injury (4).…”
Section: Introductionmentioning
confidence: 99%
“…Because it is quite long and and easily exposed, the sciatic nerve of Wistar rats is one of the most commonly used models in studies investigating neural regeneration 16 . However, Kemp 17 showed that reinnervation occurs after nervous transfer between the tibial and fibular nerves, revealing that these branches of the sciatic nerve may be used in experimental studies of peripheral nerves.…”
Section: Discussionmentioning
confidence: 99%